The Effect of Early Goal-Directed Therapy on Outcome in Adult Severe Sepsis and Septic Shock Patients: A Meta-Analysis of Randomized Clinical Trials. (August 2016) - Xu, Jing-Yuan; Chen, Qi-Hong; Liu, Song-Qiao; Pan, Chun; Xu, Xiu-Ping; Han, Ji-Bin; Xie, Jian-Feng; Huang, Ying-Zi; Guo, Feng-Mei; Yang, Yi; Qiu, Hai-Bo
Abstract : BACKGROUND: Whether early goal-directed therapy (EGDT) improves outcome in severe sepsis and septic shock remains unclear. We performed a meta-analysis of existing clinical trials to examine whether EGDT improved outcome in the resuscitation of adult sepsis patients compared with control care. METHODS: We searched for eligible studies using MEDLINE, Elsevier, Cochrane Central Register of Controlled Trials, and Web of Science databases. Studies were eligible if they compared the effects of EGDT versus control care on mortality in adult patients with severe sepsis and septic shock. Two reviewers extracted data independently. Data including mortality, sample size of the patients with severe sepsis and septic shock, and resuscitation end points were extracted. Data were analyzed using methods recommended by the Cochrane Collaboration Review Manager 4.2 software. Random errors were evaluated by trial sequential analysis (TSA). RESULTS: Nine studies compared EGDT with control care, and 5202 severe sepsis and septic shock patients were included. A nonsignificant trend toward reduction in the longest all-cause mortality was observed in the EGDT group compared with control care (relative risk, 0.89; 99% confidence interval, 0.74–1.07; P = 0.10). However, EGDT significantly reduced intensive care unit mortality in severe sepsis and septic shock patients (relative risk, 0.72; 99% confidence interval, 0.57–0.90; P = 0.0002). TSA indicated lack of firm evidence for a beneficial effect. CONCLUSIONS: In this meta-analysis, a nonsignificant trend toward reduction in the longest all-cause mortality in patients resuscitated with EGDT was noted. However, EGDT significantly reduced intensive care unit mortality in severe sepsis and septic shock patients. TSA indicated a lack of firm evidence for the results. More powered, randomized controlled trials are needed to determine the effects. Abstract : Supplemental Digital Content is available in the text.Published ahead of print April 5, 2016